Islamist Populist Nation-Building: Gradual, Ad Hoc Islamisation of the Secular Education System in Turkey - Yilmaz, Ihsan (Religions, 2022)
The founders of the secular Turkish Republic, the Kemalists used secular nationalist education to build a secular Turkish nation and to create their own version of modern pro-Western secular Turkish citizens. This paper argues that Turkey’s current ruling party, the AKP (Justice and Development Party) has been using the same system of education to create its own desired citizens with Islamist Populist ideals. This has been done without changing the secular principles of the constitution and laws on national education since there are several constraints that would prevent AKP to have open and declared pro-Sharia changes to the law. Thus, unlike many other Islamists in the other parts of the world, the paper shows that the AKP has chosen to undermine the secularity of the system, constitution, and law in an ad hoc, gradual and undeclared fashion. The paper concludes by noting that no matter the change in political actors and their ideologies, education is monopolized by the state for political purposes.